The Pharmaceutical Sector of the Western Balkan Countries - Imasheva, Aizhan; Seiter, Andreas (World Bank, Washington, DC, 2013)
There is a strong political will in the Western Balkan states to align the region's pharmaceutical legislation and practice with that of the European Union. Accordingly, recent policy changes were aimed at harmonization of policies with other European countries. Several national drug laws were updated or completely re-written in the last several years. More specifically, provisions were made for the simplification of drug registration requirements, licensing of professionals and businesses in the sector, implementation of ethics standards, price controls and reimbursement of drugs through national health insurance systems. Countries in the region have introduced various measures for cost containment, mostly through positive lists with various co-payment levels or expenditure caps for prescribing physicians. Some institutional buyers are using pooled procurement with open tenders to ensure lower prices. Nevertheless, there are still a number of challenges such as lack of enforcement of rules and standards, limited access to drugs for low income populations, inefficiencies in resource allocation and in the distribution chain, lack of control over physicians prescribing behavior and occasional conflicts between public health and industrial policy objectives. For the foreseeable future, there will be a need for further capacity building in the pharmaceutical sector, with a focus on increased oversight and higher professional standards, more efficient use of limited public resources, equity of access and rational use of medicines. Nevertheless, drug expenditure is set to grow in this region as it did in other countries in Eastern Europe, typically at a rate of about twice GDP growth, due to inevitable factors such as innovation, aging populations, increasing incomes and better access to healthcare.